Cambios identitarios de los jóvenes indígenas de Cotopaxi :Estudio de caso en la comunidad de San Antonio de Chaupi barrio Loma de Panecillo - Gavilánez Chusin, Willian Neptali (2015)
This investigation consists of three chapters that analyzes the changes identity of indigenous youth, ages 14-28 years at the San Antonio de Chaupi community and the barrio Loma de Panecillon, in Cotopaxi Province. The ethnography was the method used in this research, for which the main tools like semi-structured interviews, themed conversation, participant observation and field notes were used. This paper evidences the main factors influencing on new youth identities, such as education, media and migration is discussed. During the investigation two types of indigenous youth are differed, the young migrants to the city of Latacunga and the residents in communities. Basically, the identity changes occur in young migrants through social relations, have acquired or adapted customs alien to those experienced in communities. Although, it is important to emphasize that even in young indigenous residents are evident "new" identities. The principal changes in youth identity is the language, clothing and farming practices. Also, this investigation evidences some customs and practices that still maintain indigenous youth migrants.